ANALISIS KINERJA PENDAPATAN ASLI DAERAH KABUPATEN BUNGO - Misni Erwati; Muhammad Rizki Fajri (Jurnal Manajemen Terapan dan Keuangan, 2017)
This research aims to assess the performance of original regional income Bungo district using the ratio approach to measure local financial independence, effectiveness of local revenue, and efficiency of local revenue and trend analysis to determine trends and projections of independence ratio, effectiveness of local revenue ratio, and efficiency of local revenue ratio. The processed data is a summary of region budget of revenue and expense of the fiscal year 2010-2014 were obtained from the central statistical agency. This research used quantitive descriptive methodThe results conclude  that the level of local financial independence Bungo district  still very low which still belong to the category instructive relationship patterns, the effectiveness of local revenue has not reached effective category, and the level of efficiency of local revenue is reached very efficiency category.